A conformational switch in initiation factor 2 controls the fidelity of translation initiation in bacteria. Issue 1 (December 2017) - Caban, Kelvin; Pavlov, Michael; Ehrenberg, Måns; Gonzalez, Ruben
Abstract Initiation factor (IF) 2 controls the fidelity of translation initiation by selectively increasing the rate of 50S ribosomal subunit joining to 30S initiation complexes (ICs) that carry anN -formyl-methionyl-tRNA (fMet-tRNAfMet ). Previous studies suggest that rapid 50S subunit joining involves a GTP- and fMet-tRNAfMet -dependent "activation" of IF2, but a lack of data on the structure and conformational dynamics of 30S IC-bound IF2 has precluded a mechanistic understanding of this process. Here, using an IF2-tRNA single-molecule fluorescence resonance energy transfer signal, we directly observe the conformational switch that is associated with IF2 activation within 30S ICs that lack IF3. Based on these results, we propose a model of IF2 activation that reveals how GTP, fMet-tRNAfMet, and specific structural elements of IF2 drive and regulate this conformational switch. Notably, we find that domain III of IF2 plays a pivotal, allosteric, role in IF2 activation, suggesting that this domain can be targeted for the development of novel antibiotics. The GTP-bound form of initiation factor 2 (IF2) promotes translation initiation by accelerating 50S ribosomal subunit joining the 30S ribosomal initiation complex (30S IC). Here the authors use single-molecule FRET and ensemble rapid kinetic methods to uncover the mechanism behind IF2-mediated subunit joining.